Improving The Product Availability by Forecasting The Demand and Manage the Inventory at CV Truck Jaya - Abdurrahman, Muhammad Luqman Arif; Handayati, Yuanita (Journal of Business and Management, 2015)
Abstract. Transportation has important key on businesses. The dominant transportation in Indonesia is land transportation (Truck). If there is any disturbance on transportation, it will affect the bad impact for businesses. Therefore, the availability of truck is very important for businesses. This research choose truck supplier, CV. Truck Jaya, as a case study because without truck supplier, there will be not a transport activity and will give bad impact to businesses. CV. Truck Jaya has important role in West Java Island logistic. CV. Truck Jaya supply used truck car to small medium enterprise in West Java Area. CV Truck Jaya has a role to keep logistic in West Java running properly. This research found that CV Truck Jaya has a problem with the availability of their truck. This situation is happened because they are only using judgmental decision by the owner to forecast the demand and maintain the product availability. Judgmental decision cannot give accurate prediction, therefore there are a lot of mismatch between supply and demand This research will be conducted to determine which forecast method and inventory management system which proper to be used in CV. Truck Jaya to improve the company’s product availability. This research gives solution that the best forecasting is Croston method and best inventory management is EOQ MRP. This research give improvement to CV Truck Jaya’s out of stock condition around 33% and buys from other truck supplier around 36%.